2022
DOI: 10.3389/fmicb.2022.761670
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Surface-Exposed Lipoproteins of Leptospira Involved in Modulation of Host Innate Immune Response

Abstract: Leptospira, a zoonotic pathogen, is capable of causing both chronic and acute infection in a susceptible host. Surface-exposed lipoproteins play a major role in modulating the host immune response by activating the innate cells like macrophages and dendritic cells or evading complement attack and killing by phagocytes like neutrophils to favor pathogenesis and establish infection. In this study, we screened some surface-exposed lipoproteins known to be involved in pathogenesis to assess their possible role in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Our result suggests that the LEPIRGA interaction with the macrophages was a critical factor that contributes to the differential regulation of these OMPs, which are predicted to have adhesin properties since the expression of these proteins did not change in LEPIRGA strains incubated in medium alone. Since most of the proteins identified in our study are known to be involved in the activation of macrophages or evasion from complement system, modulation of their expression indicates an immune evasion strategy adapted by pathogenic L. interrogans serovar Icterohaemorrhagiae ( 65 , 80 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our result suggests that the LEPIRGA interaction with the macrophages was a critical factor that contributes to the differential regulation of these OMPs, which are predicted to have adhesin properties since the expression of these proteins did not change in LEPIRGA strains incubated in medium alone. Since most of the proteins identified in our study are known to be involved in the activation of macrophages or evasion from complement system, modulation of their expression indicates an immune evasion strategy adapted by pathogenic L. interrogans serovar Icterohaemorrhagiae ( 65 , 80 ).…”
Section: Discussionmentioning
confidence: 91%
“…The cytoplasmic membrane protein (LA_1499) contains a bacterial immunoglobulin-like domain 5 and might be involved in a nonclassical secretion pathway as predicted by in silico analysis ( 53 , 62 ). LipL21 is one of the abundant outer membrane lipoproteins in pathogenic L. interrogans serovar Copenhageni ( 63 ), which is highly expressed during infection and binds to Toll-like receptor 4 (TLR4) and complement regulators for modulating the innate response ( 9 , 64 , 65 ). Loa22 contains an OmpA domain and has been shown to bind to ECM components such as fibronectin and collagen and also TLR2 to induce proinflammatory response ( 66 , 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Kumar et al (2022) demonstrated that recombinant LipL21 interacts with complement negative regulator C4bp and FH, favoring serum resistance, and displays in vitro nuclease activity toward neutrophil extracellular trap (NET); LipL21 protein can modulate neutrophil function by inhibiting myeloperoxidase (MPO) activity (Vieira et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, even minor endotoxin contamination in recombinant proteins expressed in E. coli may lead to erroneous conclusions on the putative inflammatory or lytic roles of these leptospiral proteins. Considering the endotoxin contamination issues described above in Issues about endotoxin contaminations in recombinant proteins and Relevant examples from the literature sections, we reviewed different studies using recombinant Leptospira proteins ( 124 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 ). For each article, we present in Table 1 , the factsheet of the study and critically assessed the potential endotoxin contamination and conclusions about the immune functions and lytic properties of the studied recombinant proteins.…”
Section: Relevant Examples From the Literaturementioning
confidence: 99%